Comunicación de crisis y audiencias juveniles - Angulo Sabando, Josseline Jamileth (2021)
In this research project the event of the national strike of October 2019 is studied, in relation to crisis communication and youth audiences; From here the process of communication in crisis, crisis manual, messages to youth audiences, strategies used for effective communication were investigated. As a result of this investigation, it was learned that the public at that time was not satisfied with the information provided, and how the events unfolded. Once the investigation was concluded and the results of the surveys, interviews and analysis files were obtained, it was found that the previous government does not have a crisis manual and does not apply crisis communication effectively; Therefore, the country experienced 11 days of national strike in October 2019.